2009
DOI: 10.1097/sla.0b013e3181ad64a7
|View full text |Cite
|
Sign up to set email alerts
|

Bowel Obstruction Following Appendectomy

Abstract: The rate of SBO following appendectomy in adults was 2.8%, or 0.0069 cases per person-year. The greatest risk factors for developing SBO were midline incision and nonappendicitis pathology. There is no statistically significant difference in SBO rates following laparoscopic appendectomy compared with open approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 11 publications
0
48
0
2
Order By: Relevance
“…Some asymmetry, however, is due to high incidences derived from high quality studies designed to assess incidences of small bowel obstruction or enterotomy. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] That is, some smaller low quality studies reporting lower incidences were possibly not identified. Our sensitivity analyses, however, showed that our results were quite robust, so we do not expect that these smaller low quality studies would change our results.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Some asymmetry, however, is due to high incidences derived from high quality studies designed to assess incidences of small bowel obstruction or enterotomy. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] That is, some smaller low quality studies reporting lower incidences were possibly not identified. Our sensitivity analyses, however, showed that our results were quite robust, so we do not expect that these smaller low quality studies would change our results.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
“…Adhesions may cause acute abdomen by bowel obstruction and female infertility, and patients may require reoperation. [5][6][7][8][9][10][11][12][13][14] Lysis of adhesions is associated with a prolonged operative time and an increased risk of intraoperative and postoperative complications. 5 14 Most of the epidemiological knowledge of adhesions has been derived from the extensive work of the Surgical and Clinical Adhesions Research (SCAR) Group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Anderson reviewing small bowel obstruction after appendicectomy, (13) reported a cumulative risk of surgically treated small bowel obstruction after appendicectomy of 0.41% after 4 weeks, 0.63% after 1 year and 1.30% after 30 years of follow-up, compared with 0.003% at 1 year and 0.21% after 30 years of follow-up among a conservatively managed group. In another review of 1,777 patients who had an appendicectomy for acute appendicitis, the overall small bowel obstruction rate was 2.8% over an average 4.1-year follow-up (26). Laparoscopic appendicectomy is associated with less postoperative pain and a reduced hospital stay, but it also carries risks as follows: intra-operative complications (0.7% to 3.1%), postoperative complications (1.9% to 6.1%) and re-operation rates ranging from 0.7 % to 3.4% (27).…”
Section: Efficacymentioning
confidence: 99%
“…Although it is well tolerated by most patients, it can be associated with postoperative complications in a significant number of individuals: small bowel obstruction requiring surgical intervention occurs in 3% of patients undergoing appendectomy over 10 years [1]. Furthermore, more than 15% of individuals with suspected acute appendicitis have a normal appendix at laparotomy, with a higher percentage in infants, young women and elderly patients [2].…”
Section: Introductionmentioning
confidence: 99%